Spinal Injury Hospitalizations Among U.S. Army Soldiers Deployed to Iraq and Afghanistan. Issue 2 (1st February 2015) - Wojcik, Barbara E.; Curley, Kenneth C.; Szeszel-Fedorowicz, Wioletta; Stein, Catherine R.; Humphrey, Rebecca J.
ABSTRACT: This retrospective study examined spinal-related hospitalizations of U.S. Army soldiers deployed to Afghanistan and Iraq. Spinal cord injuries (SCI) and vertebral column injuries (VCI) were identified using International Classification of Disease, 9th Revision, Clinical Modification diagnosis codes. In our study, spinal hospitalizations represented 8.2% of total injury admissions. Risk factors for SCI and VCI incidences were determined using Poisson regression. Lack of previous deployment experience increased risk of having SCI by 33% and VCI by 24% in Iraq (similar increases, but not statistically significant in Afghanistan). Male soldiers had 4.85 times higher risk for SCI in Iraq and 69% higher risk in Afghanistan than female soldiers. In Afghanistan, almost 60% of spinal episodes included traumatic brain injury (TBI), compared to about 40% in Iraq. In both theaters, mild TBI accounted for more than 50% of all TBI-spinal episodes. Sixteen percent of SCI inpatient episodes in Afghanistan and 13% in Iraq were associated with paralysis, with median bed days of 46 and 33 days compared to a median of 6 days in both theaters for nonparalysis spinal injuries. The mortality rate was 2.5 times lower in Afghanistan than in Iraq.